Taco complex derived from a bis-crown ether capable of executing molecular logic operation through reversible complexation - Mandal, Amal Kumar; Das, Priyadip; Mahato, Prasenjit; Acharya, Suhash; Das, Amitava (Journal of Organic Chemistry, 2012)
As learned from natural systems, self-assembly and self-sorting help in interconnecting different molecular logic gates and thus achieve high-level logic functions. In this context, demonstration of important logic operations using changes in optical responses due to the formation of molecular assemblies is even more desirable for the construction of a molecular computer. Synthesis of an appropriate divalent as well as a luminescent crown ether based host 1 and paraquat derivatives, 2(PF6)2 and 3(PF6)2, as guests helped in demonstrating a reversible [3](taco complex) (1·{2(PF6)2}2 or 1·{3(PF6)2}2) formation in nonpolar solvent. Detailed 1H NMR studies revealed that two paraquat units were bound cooperatively by the two crown units in 1. Because of preorganization, the flexible host molecule 1 adopts a folded conformation, where each of two paraquat units remain sandwiched between the two aromatic units of each folded crown ether moiety in 1. Disassembly of the “taco” complex in the presence of KPF6 and reassembly on subsequent addition of DB18C6 was initially demonstrated by 1H NMR spectral studies, which were subsequently corroborated through luminescence spectral studies. Further, luminescence spectral responses as output signals with appropriate and two independent molecular inputs could be correlated to demonstrate basic logic operation like OR and YES gates, while the results of the three molecular inputs could be utilized to demonstrate important logic operation like an INHIBIT gate.

Tuning of multiple luminescence outputs and white-light emission from a single gelator molecule through an ESIPT coupled AIEE process - Maity, Arunava; Ali, Firoj; Agarwalla, Hridesh; Anothumakkool, Bihag; Das, Amitava (Chemical Communications, 2015)
A unique example of an ESIPT coupled AIEE process, associated with a single molecule (1), is utilized for generating multiple luminescent colors (blue-green-white-yellow). The J-aggregated state of 1 forms a luminescent gel in THF and this luminescent property is retained even in the solid state.

Tuning emission responses of a triphenylamine derivative in host-guest complexes and an unusual dynamic inclusion phenomenon - Gangopadhyay, Monalisa; Mandal, Amal K.; Maity, Arunava; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Journal of Organic Chemistry, 2016)
A newly synthesized triphenylamine derivative (1Cl(3)) shows significant differences in inclusion complex formation with two different macrocyclic hosts, cucurbit[7]uril (CB[7]) and beta-cyclodextrin (beta-CD). Detailed investigations by NMR spectroscopy reveal that CB[7] forms a 1:3 host-guest complex ([1 center dot 3{CB[7]}]Cl-3) in which three arms of 1Cl(3) are bound to three host molecules. On the other hand, beta-CD forms a dynamic 1:1 inclusion complex ([1 center dotbeta-CD]Cl-3) by binding to only one of the three arms of 1Cl(3) at a given time. The formation of a 1:1 host-guest complex with beta-CD and 1:3 host-guest complex with CB[7] was also confirmed from the results of the isothermal titration calorimetric studies. Interestingly, 1Cl(3) exhibits a rare dual emission property in solution at room temperature with the lower and higher energy bands arising from a locally excited state and an intramolecular charge-transfer transition, respectively. The difference in inclusion complex formation behavior of 1Cl(3) with the two macrocyclic hosts results in the stabilization of different emission states in the two inclusion complexes. The fundamental difference in the electrostatic surface potentials, cavity polarities, and shapes of the two macrocyclic hosts could account for the formation of the different inclusion complexes with distinct luminescence responses.

Tracking HOCl concentrations across cellular organelles in real time using a super resolution microscopy probe - Ali, Firoj; Aute, Sunil; Sreedharan, Sreejesh; Anila, H. A.; Saeed, Hiwa K.; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
BODIPY derivative, SF-1, exclusively shows a fluorescence ON response to HOCl and images endogenously generated HOCl in RAW 264.7 macrophages. Widefield and super resolution structured illumination microscopy images confirm localization in the Golgi complex and lysosomes, and hence specifically detects HOCl generated in these organelles. SF-1 is compatible with 3D-SIM imaging of individual cells.